Automated reasoning with analytic tableaux and related methods 20th International Conference, TABLEAUX 2011, Bern, Switzerland, July 4-8, 2011. Proceedings - Brünnler, Kai; Metcalfe, George (Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 20th International Conference on Automated Reasoning with Analytic Tableaux and Related Methods, TABLEAUX 2011, held in Bern, Switzerland, in July 2011.The 16 revised research papers presented together with 2 system descriptions were carefully reviewed and selected from 34 submissions. The papers cover many topics in the wide range of applications of tableaux and related methods such as analytic tableaux for various logics, related techniques and concepts, related methods, new calculi and methods for theorem proving in classical and non-classical logics, as well as systems, tools, implementations and applications; all with a special focus on hardware and software verifications, semantic technologies, and knowledge engineering